The Impact of Brochures Versus Mobile Applications on Mothers' Knowledge and Attitudes Regarding Topical Fluoride Application for Their Children - Molaasadolah, Fatemeh; Iranparvar, Parastoo; Hosseini, Alireza; Soltani, Mansooreh (Journal of Dental School, 2025)
Objective(s): Due to the high prevalence of dental caries among children, and considering the effectiveness of fluoride in caries prevention, coupled with the significant role of mothers in children's oral health, enhancing maternal knowledge about fluoride therapy can improve children's oral health. This study aimed to compare the impact of education using two methods, brochures and mobile applications, on knowledge and attitude of mothers, concerning topical fluoride application for their children. Methods: This longitudinal interventional study involved 140 mothers attending the Pediatric Dentistry Department, divided into two groups. A questionnaire regarding children's topical fluoride application was administered to them. After receiving the completed questionnaires, brochures were provided to the mothers in the first group, while a mobile application was provided to the second group. Immediately following the educational intervention, the same questionnaire was re-administered. Three months later, both groups were recalled to complete the questionnaire to assess information retention. Finally, the data were analyzed using Pearson's correlation, chi-square, analysis of variance, independent samples t-test, and Bonferroni post-hoc test (p < 0.05). Results: Mothers' knowledge and attitude significantly increased in both groups immediately after the intervention (p < 0.001). There was no significant difference in attitudes between the two groups immediately after the intervention (P = 0.17), but three months after the intervention, attitudes were higher in the mobile application group compared to the brochure group (P = 0.01). Knowledge was higher in the brochure group immediately after the intervention (p < 0.001), but three months after the intervention, it was higher in the mobile application group (p < 0.001). Conclusion: Maternal knowledge and attitudes toward topical fluoride application significantly improved following the brochure study and the mobile application use. In the long term, the mobile application demonstrated superior efficacy in enhancing knowledge and attitudes.